Degradation of Organic Matter from Stabilized Leachate by Using Zinc Sulphate as Coagulant Agent - Kamaruddin M.A.; Yusoff M.S.; Adam N.H.; Maz M.R.R.; Abdullah M.M.A.B.; Alrozi R.; Zawawi M.H. (Institute of Physics Publishing, 2023)
Analysis of variance (ANOVA); Coagulation; Leachate treatment; Microfiltration; Pore size; Sulfur compounds; Coagulant agents; Confidence interval; Discharge limit; Landfill leachates; Organic fractions; Receiving waters; Sequential treatments; Sludge volume index; Zinc compounds